Discontinued drugs in 2006: Pulmonary-allergy, dermatological, gastrointestinal and arthritis drugs - (:unkn) unknown (My University, 2007)
This perspective is the second in a series discussing drugs dropped from development in 2006, with a focus on pulmonary-allergy, dermatological, gastrointestinal and arthritis drugs. A survey of discontinued drugs from 2006 is provided, based on data from the Pharmaprojects database, along with an analysis of biology, mechanisms of action and economic considerations in developing new drugs. © 2007 Informa UK Ltd.
Keywords: Arthritis; Asthma; Atopic eczema; Discontinued drugs; New drugs; Psoriasis